Asymmetric flow field flow fractionation for the investigation of caseins cross-linked by microbial transglutaminase. (July 2019) - Abbate, Raffaele Andrea; Raak, Norbert; Boye, Susanne; Janke, Andreas; Rohm, Harald; Jaros, Doris; Lederer, Albena
Abstract: The cross-linking of caseins with microbial transglutaminase (mTGase) was investigated using asymmetric flow field flow fractionation in combination with static and dynamic light scattering detections (AF4-MALS-DLS). This approach allows determining molar mass, molecular size, scaling properties, and apparent densities of casein aggregates prior to and after enzymatic treatment. The results show that, as a consequence of non-covalent interactions, casein molecules associate to form elongated aggregates with a molar mass ( M w ) ranging from approx. 4 × 10 5 to 1.2 × 10 6  g mol −1, and a mean radius of gyration ( R g, z ) of approx. 16 nm. Upon enzymatic treatment with mTGase, casein aggregates become more compact as M w increases but R g decreases with ongoing cross-linking reaction. In contrast, the hydrodynamic radius ( R h ) distribution determined by online DLS is rather unaffected by enzymatic cross-linking, indicating that mTGase cross-links casein molecules mainly within distinct aggregates. Furthermore, extensive enzymatic treatments with mTGase change the molecular shapes of casein aggregates towards more compact and denser spherical structures. Graphical abstract: Image 1 Highlights: Casein cross-linking studied by asymmetric flow field flow fractionation and light scattering. Casein molecules associate to form elongated aggregates. Enzymatic treatment leads to compact casein aggregates with the incubation time.